Song Is More Memorable Than Speech Prosody: Discrete Pitches Aid Auditory Working Memory - Haiduk, Felix; Quigley, Cliodhna; Fitch, W. Tecumseh (Frontiers in Psychology, 2020)
Vocal music and spoken language both have important roles in human communication, but it is unclear why these two different modes of vocal communication exist. Although similar, speech and song differ in certain design features. One interesting difference is in the pitch intonation contour, which consists of discrete tones in song, versus gliding intonation contours in speech. Here, we investigated whether vocal phrases consisting of discrete pitches (song- like) or gliding pitches (speech- like) are remembered better, conducting three studies implementing auditory same-different tasks at three levels of difficulty. We tested two hypotheses: that discrete pitch contours aid auditory memory, independent of musical experience ("song memory advantage hypothesis"), or that the higher everyday experience perceiving and producing speech make speech intonation easier to remember ("experience advantage hypothesis"). We used closely matched stimuli, controlling for rhythm and timbre, and we included a stimulus intermediate between song-like and speech-like pitch contours (with partially gliding and partially discrete pitches). We also assessed participants’ musicality to evaluate experience-dependent effects. We found that song-like vocal phrases are remembered better than speech-like vocal phrases, and that intermediate vocal phrases evoked a similar advantage to song-like vocal phrases. Participants with more musical experience were better in remembering all three types of vocal phrases. The precise roles of absolute and relative pitch perception and the influence of top-down vs. bottom-up processing should be clarified in future studies. However, our results suggest that one potential reason for the emergence of discrete pitch - a feature that characterises music across cultures - might be that it enhances auditory memory.